Pengaruh Dimensi Aktivitas Pemasaran Media Sosial Terhadap Niat Beli Produk Domino’s Pizza Di Bandar Lampung - Bintang Abyan Dwi Anggoro; Driya Wiryawan; Nuzul Inas Nabila (Shofanah Media Berkah, 2023)
The advancement of technology has transformed the way humans seek information, communicate, and convert various aspects into digital forms. Social media has become a popular platform for content sharing and communication, heavily reliant on internet progress. The use of social media in marketing has become crucial for companies in their promotional efforts. In Indonesia, with a large internet user population, marketing activities through social media play a significant role in influencing consumer purchasing intentions. An example is Domino's Pizza, a company utilizing social media for product promotion. This study aims to examine the influence of dimensions of social media marketing activities on purchasing intentions towards Domino's Pizza products in Bandar Lampung. Purchasing intention signifies the desire or inclination to buy a product and is formed before the actual purchasing process. Social media marketing activities refer to actions undertaken by businesses to promote products or services on social media platforms. This research employs primary data collected from questionnaires with Likert scale measurements. The sample for this study consists of 190 Domino's Pizza consumers residing in Bandar Lampung. The data analysis utilized is multiple linear regression through SPSS 26 software. The research findings reveal that the social media marketing activity variables encompassing entertainment, interaction, trendiness, customization, and word-of-mouth exert influence on product purchasing. The Hiburan variable is also shown to be the social media marketing dimension with the highest level of significance in impacting purchasing intentions.